2014
DOI: 10.1617/s11527-014-0398-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the flexural deflections of concrete beam reinforced with Basalt FRP bars

Abstract: This paper presents an experimental study of the flexural defections of concrete beam reinforced with basalt FRP bars. Six concrete beams with different BFRP reinforcement ratio and one comparative beam reinforced with steel rebar are tested in laboratory. Numerical simulations using sectional analysis method and spatial FEM are performed. The experimental results can fit well with numerical simulation results. Analysis and experimental results in the literature collected indicate that the ACI-440.1R-06 equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Experiments have shown that the width of the opening of oblique cracks did not exceed admissible values at average values of design factors. These data are consistent with the results of study [29].…”
Section: ( )supporting
confidence: 93%
“…Experiments have shown that the width of the opening of oblique cracks did not exceed admissible values at average values of design factors. These data are consistent with the results of study [29].…”
Section: ( )supporting
confidence: 93%
“…The basalt fibers are non-toxic, natural, eco-friendly, and environmentally safe [33][34]. Characterized by their relatively low price, superior modulus, high strength, excellent stability, and resistance to chemical erosion and high temperatures [34][35], basalt fibers possess higher material properties (such as tensile strength and elastic modulus) than glass fibers and are far cheaper than carbon fibers [36][37][38][39]. Therefore, basalt FRP (BFRP) composites are considered as feasible and sustainable alternatives to conventional FRP composites for future strengthening applications of RC structures.…”
Section: Introductionmentioning
confidence: 99%
“…Basalt fibre reinforced polymers (BFRP) are advanced composite materials, and extensive research activity has been devoted to their production and possible applications in different fields of engineering, including civil engineering (Fiore et al [1]). The use of BFRP bars in concrete structural elements was investigated by Tharmarajah et al [2], Zhang et al [3], High et al [4], Elgabbas et al [5], Fan & Chang [6,7] and applied with self-compacting concrete (SCC) in Thompson's bridge in Northern Ireland (Taylor et al [8]). …”
Section: Introductionmentioning
confidence: 99%